New taxa of Carpomyini, with special emphasis on Goniglossum (Diptera: Tephritidae: Trypetinae) - Freidberg, Amnon (Zootaxa, 2016)
Goniglossum Rondani, hitherto a monobasic genus, is reinstated from synonymy under Carpomya Costa. A second species, Goniglossum liat n. sp., is described nearly two centuries after the description of the first species and 160 years after the description of Goniglossum. G. liat is described from Israel (also known from Turkey) and compared with G. wiedemanni (Meigen), an essentially European species, which is the type-species of Goniglossum and the only other known congener. The two species differ in details of the mesonotal and pleural color pattern (e.g., tip of scutellum with three small black spots in G. wiedemanni, whereas with one large spot in G. liat), structure of the male and female terminalia (e.g., the aculeus of G. wiedemanni is distinctly narrower apically than that of G. liat, and its tip has significantly fewer teeth), and host plant associations (Bryonia alba L. and B. dioica Jacq. are hosts of G. wiedemanni, whereas Bryonia cretica L. and B. syriaca Boiss. are hosts of G. liat). Myiopardalis Bezzi is also reinstated from synonymy under Carpomya. C. tica Norrbom, originally described in Carpomya, is transferred to Norrbomella, new genus, as its type and only included species.